Recurrence of tubercular choroiditis following anti-SARS-CoV-2 vaccination. Issue 3 (May 2023) - Arora, Atul; Handa, Sabia; Singh, Simar Rajan; Sharma, Aman; Bansal, Reema; Agrawal, Rupesh; Gupta, Vishali
Purpose: To report recurrence of tubercular choroiditis following anti-SARS-CoV-2 vaccination in two patients with quiescent disease activity for more than a year. Methods: Retrospective observational case reports. Results: Two patients (one female and one male) under follow-up for posterior uveitis having stable course with absence of ocular inflammation for more than a year presented with recurrence of choroiditis lesions 2–6 weeks following anti-SARS-CoV-2 vaccination. Both the patients were managed with intravitreal dexamethasone implant (Ozurdex®, Allergan, Inc., Irvine, CA, USA) and showed resolution of choroiditis lesions upon follow-up. Conclusions: Acute onset recurrence of inflammation, in absence of any change in health status or treatment suggests the potential role of vaccination being the trigger of this reactivation. Given large-scale vaccination against novel coronavirus- SARS-CoV-2, careful vigilance is warranted to pick up the disease recurrence in patients with posterior uveitis.